1981
DOI: 10.1007/bf01054857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary nickel on survival and growth of mallard ducklings

Abstract: Mallard (Anas platyrhynchos) ducklings were fed nickel sulphate in their diet from day one to 90 days of age. Ducklings fed 1,200 ppm nickel began to tremor and show signs of paresis after 14 days of dosage (age) and 71% of this group died within 60 days of age. Birds fed 1,200 ppm nickel weighed significantly less (P less than 0.05) at 28 days of age than birds fed the other diets. Weights of ducklings fed untreated food or dietary dosages of 200 and 800 ppm nickel diets were not significantly different (P le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Grasshoppers are a major component of arthropod biomass (Devkota & Schmidt 2000), and the concentrations of Ni observed in their tissues approach the level at which mammals and birds become unable to regulate their absorption and excretion of this element (Outridge & Sheuhammer 1993). The concentrations found in the "other invertebrates" category could be acutely toxic to wildlife (Cain & Pafford 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Grasshoppers are a major component of arthropod biomass (Devkota & Schmidt 2000), and the concentrations of Ni observed in their tissues approach the level at which mammals and birds become unable to regulate their absorption and excretion of this element (Outridge & Sheuhammer 1993). The concentrations found in the "other invertebrates" category could be acutely toxic to wildlife (Cain & Pafford 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The NOAEL dose is approximately 10 times greater than the dose to mallards given H-S pellets and the LOAEL dose is close to 700 times greater than the H-S dose. Furthermore, all birds that showed effects of the Ni exposure had liver and kidney residues at least 10 times higher (Cain and Pafford, 1981) than those detected in H-S dosed birds.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, verification of receipt of a nontoxic dose of Ni from ingestion of H-S shot is found by comparing exposure to ducklings fed diets containing highly soluble nickel sulfate (Cain and Pafford, 1981). These authors found no effects on duckling survival or growth when birds were fed 176 ppm Ni in the diet (determined to be the no observable adverse effects level [NOAEL]).…”
Section: Discussionmentioning
confidence: 99%
“…Doses of 21.4 mgkgday administered as nickel sulfate in the diet had no adverse effects on weight gain after 4 weeks. Mallard ducklings on diets with 2800 ppm nickel would be adversely affected (Cain and Pafford, 1981). Selenium Selenium (Se) has a combination of attributes which make it an unusual pollutant (EPA 1987).…”
Section: G13-93mentioning
confidence: 99%